The potential of atractylodin-loaded PLGA nanoparticles as chemotherapeutic for cholangiocarcinoma - Nadda Muhamad (2020)
© 2020, Asian Pacific Organization for Cancer Prevention. Backgrounds: The anti-cholangiocarcinoma (CCA) activity of atractylodin isolated from Atractylodes lacea (Thunb.) DC. has previously been demonstrated both in vitro and in vivo. However, the compound is insoluble in water and must be dissolved in organic solvent which might be harmful to human body. The aim of the study was to develop atractylodin-loaded poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) (ALNPs) and to investigate its cytotoxic activity against CCA. Methods: The ALNPs were prepared using PLGA MW 12,000 and 48,000 by solvent displacement methods. Particle size, polydispersity index (PDI), zeta potential, encapsulation efficiency (%EE) and loading efficiency (%LE) as well as drug releasing profile of ALNPs were characterized. The selected ALNPs formulation was then investigated cytotoxic activity against CCA cell lines, CL-6 and HuCC-T1. Results: The ALNPs preparation was achieved using PLGA MW 12,000 (ALNPs-1) with mean (±SD) values of particle diameter, PDI and zeta potential of 158.13±0.21 nm, 0.076±0.003, and (-) 23.80± (-) 0.75 mV, respectively. The transmission electron microscopy (TEM) showed spherical morphology of NPs. The %EE and %LE were 50.16±1.77% and 2.22±0.08%, respectively. The release of atractylodin from ALNPs-1 in PBS was up to 88% in 72 h. The potency of ALNPs-1 cytotoxic activity including selectivity against CCA cell line, CL-6, were about twice of the unformulated atractylodin after 24 h of exposure (IC50: 29.28 vs 56.36 μg/mL, selectivity index 2.99 vs 1.50). Conclusion: ALNPs were successfully prepared by solvent displacement method using PLGA MW 12,000 (ALNPs-1) with suitable pharmaceutical properties and cytotoxic activity against CCA. However, nano-formulation with improved pharmaceutical properties (higher %EE and %LE) and cytotoxic activity (improved selectivity to CCA) should be further developed for potential used as drug delivery systems for the treatment of CCA.